The Effect of the Application of Geogebra Software Android Version on the Mathematical Ability of Politeknik Ilmu Pelayaran Makassar Cadets - Fitriani Fitriani; Welem Ada'; Zulkaidah Nur Ahzan (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2026)
Mathematics is used in various aspects of life, including the maritime and marine world. Mathematical concepts are widely used to solve problems in this field. Understanding abstract mathematical concepts requires a tool to bridge these concepts into concrete forms. The aim of this study is to determine the effect of using the Android version of GeoGebra software in improving the mathematical abilities of cadets. GeoGebra is a comprehensive and easy-to-use mathematical software. A study conducted on cadets at Politeknik Ilmu Pelayaran Makassar found that the use of the GeoGebra application had a positive impact on their understanding of mathematical material. This was demonstrated by inferential statistics tests and supported by the cadets' responses to the application's use in learning.